Od histerii do pourazowego zespołu stresu - z historii badań nad przemocą - Brągiel, Józefa (Wydawnictwo Naukowe UAM, 2001)
In the article the history of the survey concerning violence, was presented starting with the period of searching for the sources of hysteria, conducted by J. M. Charcot and Z. Freud through battered child syndrome and the role played by military psychologists and feminists in searching for and describing post-traumatic stress disorder as a medical case.
Starting with hysteria, ending with post-traumatic stres disorder. From the history of survey concerning violence